Ectrodactyly in a Beagle: surgical management - Salinas, Eben A. (2018)
The case of a 5-month-old female Beagle with lameness of the right anterior limb and a separation defect between the second and third fingers is reported. In the radiographic examination, hypoplasia of the carporradial bone and of the second metacarpal, and absence of the first finger was observed. In addition, the patient presented a cleft with soft tissue content between the second and third metacarpal. The findings were compatible with unilateral ectrodactyly. Reconstructive surgery was performed through a pancarpal arthrodesis, with cancellous bone filling and using an external skeletal fixation system. The limb’s function was completely restored at 10 weeks.